2006
DOI: 10.1177/0363546505279918
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Risk Factors for the Development of Achilles Tendon Overuse Injury

Abstract: The strength of the plantar flexors and amount of dorsiflexion excursion were identified as significant predictors of an Achilles tendon overuse injury. A plantar flexor strength lower than 50.0 N.m and dorsiflexion range of motion higher than 9.0 degrees were possible thresholds for developing an Achilles tendon overuse injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
180
5
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(196 citation statements)
references
References 57 publications
7
180
5
4
Order By: Relevance
“…24 A more recent study prospectively identified that decreased plantar flexion torque as tested on an isokinetic dynamometer (30°/s and 120°/s) with the knee extended was a discriminating factor between Belgium military recruits who developed (n = 10) and those who did not develop (n = 59) Achilles tendinopathy during 6 weeks of basic training. 79 At 30°/s and 120°/s, the uninjured group generated 17.7 and 11.1 more Nm, respectively, when compared to the group that ultimately developed Achilles tendinopathy. 79 Because this study focused on male military recruits, this finding may be specific to young individuals with low plantar flexion strength levels (50 Nm) pretraining.…”
Section: Abnormal Subtalar Range Of Motionmentioning
confidence: 92%
See 4 more Smart Citations
“…24 A more recent study prospectively identified that decreased plantar flexion torque as tested on an isokinetic dynamometer (30°/s and 120°/s) with the knee extended was a discriminating factor between Belgium military recruits who developed (n = 10) and those who did not develop (n = 59) Achilles tendinopathy during 6 weeks of basic training. 79 At 30°/s and 120°/s, the uninjured group generated 17.7 and 11.1 more Nm, respectively, when compared to the group that ultimately developed Achilles tendinopathy. 79 Because this study focused on male military recruits, this finding may be specific to young individuals with low plantar flexion strength levels (50 Nm) pretraining.…”
Section: Abnormal Subtalar Range Of Motionmentioning
confidence: 92%
“…79 At 30°/s and 120°/s, the uninjured group generated 17.7 and 11.1 more Nm, respectively, when compared to the group that ultimately developed Achilles tendinopathy. 79 Because this study focused on male military recruits, this finding may be specific to young individuals with low plantar flexion strength levels (50 Nm) pretraining. In other work, Silbernagel and colleagues 118 reported that subjects with Achilles tendinopathy (n = 42) had a decreased capacity to perform a maximal concentric heel raise, as well as a maximal eccentric-concentric heel raise, when comparing the affected to the unaffected or least affected side (when the pathology was present bilaterally).…”
Section: Abnormal Subtalar Range Of Motionmentioning
confidence: 92%
See 3 more Smart Citations